EVALUATION OF QUALITY IMPROVEMENT OF CEMENT CONCRETE WORKS ROAD PENYINGGAHAN - MUARA PAHU DISTRICT WEST KUTAI - EKA, ISDIAN (KURVA S JURNAL MAHASISWA, 2014)
Concrete roads are typically used for roads with functional hierarchy in the arteries that are both outside and inside the city to serve the traffic loads are heavy and solid. Maintenance of concrete roads can be said to be nil although initially higher costs compared to asphalt roads always require regular maintenance, periodic maintenance, and upgrading of roads.Intent implementation study to determine the performance of the quality of the concrete on the implementation of the cement concrete work. While the purpose of 1). To determine the performance of the cement concrete implementation of the work on road building activities Penyinggahan - Muara Pahu. 2). Knowing the characteristics of the concrete compressive strength of cement concrete implementation work in the field. 3). To find out the cause of the decline in the value of the compressive strength of concrete after casting implemented. Results of calculation analysis, discussion and concrete compressive strength test results can concrete performance standard deviation of the results of the analysis plan (SPlant) = 30.00 Kg/cm2 while the results of the field test sample standard deviation (SField) = 39.434 K /cm2, for the implementation of quality field mixture and mix supervision should be further improved when foundry (SPlant > SField). Results of testing the compressive strength of concrete results foundry work in the field gained an average compressive strength (f'cr) = 290.556 Kg/cm2, standard deviation (S) = 39.434 Kg / cm2, and the characteristic concrete compressive strength (f'c) = 225.894 Kg/ cm2.